1993
DOI: 10.1093/oxfordjournals.humrep.a138231
|View full text |Cite
|
Sign up to set email alerts
|

Infertility: Beta-1 integrin cell adhesion molecules in the endometrium of fertile and infertile women

Abstract: In order to investigate whether the endometrium of women with unexplained infertility differs immunologically from the endometrium of normal fertile women, a panel of six monoclonal antibodies was used to characterize the presence of the beta 1-integrins or very-late-activation antigens (VLA) in the different endometrial compartments. Precisely timed endometrial biopsies at 4, 7, 10 and 13 days following the luteinizing hormone surge were obtained from 24 normal fertile women (group I) and 24 women suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 0 publications
0
50
0
4
Order By: Relevance
“…The distribution of different α and β integrin subunits in human endometrial tissues at different stages of the menstrual cycle has been determined by using immunohistochemistry. These studies suggest that some integrins normally undergo spatial and temporal changes with expression in the cycling endom e trium , a n d t ha t disruptio n o f this expression pattern may be associated with certain types of infertility in women [16][17][18].…”
Section: Integrins and Endometriummentioning
confidence: 94%
See 3 more Smart Citations
“…The distribution of different α and β integrin subunits in human endometrial tissues at different stages of the menstrual cycle has been determined by using immunohistochemistry. These studies suggest that some integrins normally undergo spatial and temporal changes with expression in the cycling endom e trium , a n d t ha t disruptio n o f this expression pattern may be associated with certain types of infertility in women [16][17][18].…”
Section: Integrins and Endometriummentioning
confidence: 94%
“…Several studies have confirmed the presence of β1 integrins on human endometrium and demonstrate that integrin expression is a dynamic process related to the menstrual cycle [16][17][18]. The distribution of different α and β integrin subunits in human endometrial tissues at different stages of the menstrual cycle has been determined by using immunohistochemistry.…”
Section: Integrins and Endometriummentioning
confidence: 97%
See 2 more Smart Citations
“…49 İntegrinlerin α4 ve β3 subünitlerinin uterin reseptivitenin maksimum olduğu dönemde birlikte eksprese oldukları görülmüştür. 35,42,43,49 Özellikle α4β3 integrinler implantasyon zamanı açık pencere dönemi için çok daha güvenilir bir belirleyicidirler ve bunların ekspresyonları erken gebelik dönemine uzanır.…”
Section: Açiklanamayan İnferti̇li̇te Ve İntegri̇nlerunclassified